CLASSIFICATION OF THE IMAGE OF THE MOTHER IN WILLIAM FAULKNER’S AS I LAY DYING AND O‘TKIR HOSHIMOV’S DUNYONING ISHLARI - Khudaynazarova Mahbuba Shavkat qizi,; Djalilova Z.O., (PEDAGOGS, 2025)
This paper explores the representation of the mother figure in William Faulkner’s As I Lay Dying and O‘tkir Hoshimov’s Dunyoning Ishlari. Both novels depict the mother as a central but complex character whose role extends beyond traditional maternal duties. Through a comparative literary approach, this study classifies the mother’s image into three primary categories: sacrificial mother, absent mother, and symbolic mother. By analyzing Addie Bundren and Sadbar opa, this paper reveals how these authors present motherhood in relation to family, society, and existential struggles. The findings demonstrate that while Faulkner portrays a psychologically tormented mother with a modernist approach, Hoshimov presents a deeply compassionate yet tragic mother within a realist framework.